ANALYSIS OF MATHEMATICAL CREATIVE THINKING ABILITY OF MIDDLE SCHOOL STUDENTS ON DATA PRESENTATION MATERIALS: ANALISIS KEMAMPUAN BERPIKIR KREATIF MATEMATIS SISWA SMP PADA MATERI PENYAJIAN DATA - Sari, Rika Mulyati Mustika; Iqbal, Rahmat (Department of Mathematics Education Faculty of Tarbiyah and Teacher Training Universitas Islam Negeri Alauddin Makassar, 2023)
This article is the result of research that aims to find out how students' mathematical creative thinking abilities solve questions related to data presentation material. This research uses a quantitative approach with descriptive methods. Data presentation material is one of the mathematical materials contained in the basic competencies that must be mastered by class VII students and is closely related to everyday life. In this study, the population consisted of students of class VII at a state junior high school in the city of Tangerang for the 2022/2023 academic year. Selection of the sample utilizing purposive sampling with 34 students of class VII-D. Data collection techniques by giving creative thinking tests in the form of descriptions that were previously validated. The results of this study showed that the students' mathematical creative thinking test scores were 20.6% in the high category, 67.6% in the medium category, and 11.4% in the low category.